STUDENTS’ PERCEPTION TOWARD THE INTEGRATION OF TECHNOLOGY TO IMPROVE MULTILITERACIES COMPETENCE IN EFL CLASSROOMS - Kustini, Siti; Herlinawati, Herlinawati; Indrasary, Yoenie (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2020)
The rapid development of information and communication technology in the 21st century undoubtedly has profound impacts on human lives and dramatically transforms education. This research aimed at finding out students? perceptions on the integration of technology to improve multiliteracies in EFL teaching. This study employed explanatory sequential mixed method in which the data were obtained through questionnaire, interviews, and classroom observations. The results indicated that vast majority of the students supported to the use of technology in the teaching and learning practices (90.6%) for the reasons that technology helped them acquire lots of resources in their learning (89.5%) and boost their motivation (86.5%). Regarding with the students? perceived technology level, they believed that they had good skills in using word-processing, spreadsheet, and presentation program (50%). They also could use communication tools (56.3%), social media (61.5%), authoring tools (52.1%), desktop publishing (57.3%), and creating video (57.3%). In terms of the perceived barriers to integrating technology, the data indicated that the biggest constraint that the students had was the lack of or limited internet access in the their school environment (42.7%), followed by the limited to produce digital projects (39.6%). In addition, the findings show that technology was utilized as a tool for accomplishing the tasks given by the teachers and helped the students gather information from online resources and provided them more understanding about the topic learned in the classroom